Regionalism vs Universalism: Architectural Imports in Developing Countries - DOSTOĞLU, NESLİHAN (O.D.T.Ü., 1990)
"In this paper, issues of 'regionalism/universalism', 'traditional/modern','old/new' will be evaluated first in general terms, and then giving examplesof 'architectural imports' in three developing countries, Turkey, India andBrazil, discrepancies between the architects' expectations and the realitywill be emphasized. Our basic hypothesis in this paper is that one of the ma-jor criteria for designing and implementing a healthy physical environmentis to envision the future simultaneously with the past. In other words, theconception of a 'new' environment since values and culture are an accumula-tion of all the experiences, abilities and traditions in societies throughouthistory.Issues of 'regional ism/universalism', 'tradition/modern', 'old/new' havegained new dimensions after the third quarter of the nineteenth century be-cause architects, who were traditionally responsible for the design and con-struction of buildings for wealthy clients with similar values as themselvesuntil the Industrial Revolution, have been confronted with the problem ofproducing settings and objects for the daily use of masses, since then. Inthis period of rapid industrialization and significant social changes, archi-tects have been faced with value dilemmas originating from the change intypes of clients and the demand for new types of buildings. The gap betweenarchitects and user clients widened in this period, and a strong dissatisfac-tion arose in relation to the built environment since the emerging productswere not suitable to the values and needs of the users. Dissatisfaction tended to increase more in cases when the aechitect was asked to design for usersfrom a defferent culture than his own because many architects believed inthe universality of the application of prototypes and thus proposed Western'architectural imports' for countrues with different socio-economic andcultural structures. In fact, an observation of the housing areas in differentregions of the world demonstrates that although vernacular buildings andsquatter housing units, which may be define as a special type and phase ofvernacular architecture, and their respective settlements reflect an accu-mulation of the experience, abilities and traditions of related societies,many housing units and areas designed by architects show no trace of such anaccumulation. Mass housing areas which have been proposed as alternativesto squatter housing areas in Turkey, Chandigarh new town in India and Bra-zil, all of which can be given as examples of architectural imports, embodymany descrepancies between the expectations of their planners and the actu-al situation. This paper will reveal these discrepancies and will argue thatvernacular architectrue has the potentiality of satisfying the interests,goals and values of the users, and thus bears lessons for contemporary ar-chitects who care about the livability of the environments they create. Thisdoes not imply that architects should literally copy the past, but rather it isan invitation to perceive "prototypes which make individual interpretationsof the collective patterns possible"."